Cognitive impairment in the preclinical stage of dementia in FTD-3 CHMP2B mutation carriers: a longitudinal prospective study. Issue 2 (10th November 2012) - Stokholm, Jette; Teasdale, Thomas W; Johannsen, Peter; Nielsen, Jorgen E; Nielsen, Troels Tolstrup; Isaacs, Adrian; Brown, Jerry M; Gade, Anders
Abstract : Objective and methods: A longitudinal study spanning over 8 years and including 17 asymptomatic individuals with CHMP2B mutations was conducted to assess the earliest neuropsychological changes in autosomal dominant neurodegenerative disease frontotemporal dementia (FTD) linked to chromosome 3 (FTD-3). Subjects were assessed with neuropsychological tests in 2002, 2005 and 2010. Results: Cross-sectional analyses showed that the mutation carriers scored lower on tests of psychomotor speed, working memory, executive functions and verbal memory than a control group consisting of not-at-risk family members and spouses. Longitudinal analyses showed a gradual decline in psychomotor speed, working memory capacity and global executive measures in the group of non-demented mutation carriers that was not found in the control group. In contrast, there were no significant group differences in domain scores on memory or visuospatial functions. On an individual level the cognitive changes over time varied considerably. Conclusion: Subjects with CHMP2B mutation show cognitive changes dominated by executive dysfunctions, years before they fulfil diagnostic criteria of FTD. However, there is great heterogeneity in the individual cognitive trajectories.